Language attrition and heritage language reversal in returnees - Flores, Cristina (2021)
The present chapter provides an overview of the main questions investigated in research on bilingual returnees. Returnees are second/third generation speakers who grow up in a migration setting and move back to their families’ country of origin at a certain moment of their life. On the one hand, research on returnees focuses on dominant language attrition, i.e., on the linguistic changes that affect the previous societal language after moving to the homeland. On the other hand, it targets L1/HL development after immersion in the L1/HL environment and possible outcomes of heritage language reversal. In addition to the focus on language development, we discuss the pedagogical and sociological implications of return to the country of origin, which go hand in hand with changes to the returnee’s language competence.